2020
DOI: 10.1002/wps.20802
|View full text |Cite
|
Sign up to set email alerts
|

Nature and prevalence of combinations of mental disorders and their association with excess mortality in a population‐based cohort study

Abstract: The nature and prevalence of combinations of mental disorders and their associations with premature mortality have never been reported in a comprehensive way. We describe the most common combinations of mental disorders and estimate excess mortality associated with these combinations. We designed a population‐based cohort study including all 7,505,576 persons living in Denmark at some point between January 1, 1995 and December 31, 2016. Information on mental disorders and mortality was obtained from national r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(58 citation statements)
references
References 30 publications
3
55
0
Order By: Relevance
“…Additionally, it can fractionate which disorders contribute to overall disability for different sets of mental and substance use disorders. This finding complements a publication 22 based on data from Danish health registers that comprehensively describes the prevalence and associated mortality of different combinations of mental disorders. For some disorders, such as schizophrenia, the HeLP corresponds approximately to the disability weight for the given disorder, whereas for other disorders a large proportion of the HeLP is explained by non-index comorbid mental and substance use disorders.…”
Section: Discussionsupporting
confidence: 74%
“…Additionally, it can fractionate which disorders contribute to overall disability for different sets of mental and substance use disorders. This finding complements a publication 22 based on data from Danish health registers that comprehensively describes the prevalence and associated mortality of different combinations of mental disorders. For some disorders, such as schizophrenia, the HeLP corresponds approximately to the disability weight for the given disorder, whereas for other disorders a large proportion of the HeLP is explained by non-index comorbid mental and substance use disorders.…”
Section: Discussionsupporting
confidence: 74%
“…Another cross-sectional survey of college students found a strong positive interaction effect between anxiety disorder and depression (44). A large cohort study also showed that 40% individuals who had mental disorders were diagnosed with more than one disorder type (46). Our findings indicated the importance of early detection and intervention of mental health symptoms and suicidal behavior among high risk population.…”
Section: Discussionsupporting
confidence: 54%
“… 12 , 13 , 14 In addition, they show increased service utilization (eg emergency room visits, hospitalizations) and premature mortality. 12 , 13 , 14 , 15 …”
Section: Introductionmentioning
confidence: 99%
“…Regarding mortality rates, both schizophrenia and SUD are associated with premature death, with comorbidity showing additive effects. 11 , 15 , 16 However, although some substances such as alcohol, heroin and cocaine are considered more lethal compared to other substances such as cannabis, prospective studies have provided conflicting results [ie increased 11 , 12 , 16 , 17 and decreased 18 mortality] or did not take into account that morbidity and mortality might be increased by multiple drug use. 19 …”
Section: Introductionmentioning
confidence: 99%